Determinants of Employment Social Security Participation among Informal Workers: Evidence from a Cross-Sectional Study in Riau - Lira Mufti Azzahri Isnaeni; Putri Ayuni Alayyannur; Prasetyawati (Academic Bright Collaboration, 2026)
Purpose – Expanding BPJS Ketenagakerjaan coverage in Indonesia remains difficult, especially among informal workers not enrolled through mandatory employer schemes.Scholars note that both cognitive and emotional factors probably shape voluntary enrollment in social protection, but evidence linking these dimensions to employment-based insurance remains scarce. Methods – The research is a type of quantitative research with a cross-sectional design used to explore how knowledge, attitudes, and beliefs correlate with the participation of informal workers in the BPJS Employment program. A cross-sectional survey of 390 purposively sampled informal-sector participants was conducted. Trained enumerators collected data with a structured questionnaire, which was then analysed by multiple linear regression. Findings –Regression findings indicate that knowledge (B = 0.320, p < 0.001), attitude (B = 0.410, p < 0.001), and trust (B = 0.500, p < 0.001) each positively predict enrollment, with trust showing the strongest effect. The global model is significant (F = 28.350, p < 0.001), thus the three variables together account for a meaningful share of the variance. Enhancing informal workers' uptake of BPJS Ketenagakerjaan demands more than spreading facts; it also calls for cultivating supportive attitudes and building trust in the scheme's agencies Research implications – This study points to multi-faceted approaches, education, direct outreach, and reputation strengthening, that respect the unique patterns and challenges of the informal labour sector. Originality – Its approach specifically examines the determinants of informal sector workers' participation in employment social security programs in Indonesia through a comprehensive cross-sectional study design. This research makes a novel contribution by integrating sociodemographic, economic, social security literacy, and occupational risk perception variables into a single empirical analytical framework rarely explored simultaneously in the context of informal workers.